HOMESCHOOLING AND ISLAMIC EDUCATION IN INDONESIA - Sri Mulyani Nasution; Ifham Choli (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Homeschooling which is also called home education is education for children that is carried out at home and is specifically given by a teacher or a professional tutor. Homeschooling in the modern sense is an alternative to formal education in developed countries. In other words, the practice of homeschooling moves schools from a public area to a more private area, namely to the home. There are many pros and cons regarding this issue. To understand more about the problems surrounding home schooling, through library research, it is tried to be traced. From the results of the library search, it is concluded that homeschooling seems to be more recommended for developed countries or parents who understand and control the world of education. This concerns teaching and learning facilities and infrastructure that must be truly adequate for the success of this program. Homeschooling yang juga disebut pendidikan di rumah merupakan pendidikan bagi anak-anak yang dilaksanakan di rumah dan secara khusus diberikan oleh guru atau seorang tutor professional. Homeschooling dalam pengertian modern, merupakan alternatif pendidikan formal di negara-negara maju. Dengan kata lain, praktek homeschooling memindahkan sekolah dari area umum ke area yang lebih privat, yakni ke rumah. Pro-kontra banyak bermunculan berkenaan dengan isu ini. Untuk memahami lebih lanjut mengenai permasalahan seputar home schooling, melalui penelitian kepustakaan dicoba ditelusuri. Dari hasil penelusuran Pustaka, disimpulkan bahwa homeschooling tampaknya lebih direkomendasikan bagi negara yang sudah maju atau orangtua yang memahami dan menguasai dunia Pendidikan. Hal ini menyangkut sarana dan prasarana belajar-mengajar yang harus benar-benar memadai demi suksesnya program ini.